The Concept Of Character Education On Morality And Ethics (Comparison Of The Thoughts Of Islamic And Western Figures) - Puput Laila Hanum; Ahmad Saifullah (UNIVERSITAS PAKUAN, 2025)
Amidst the challenges of globalization and rapid social change, this comparative understanding provides a holistic insight into integrating universal values and cultural and religious characteristics in character education. The high moral and ethical crisis that is increasingly evident in various societies, this comparative study certainly supports the formation of a generation with noble character and responsibility in an increasingly complex global context. The comparison of character education approaches from an Islamic and Western perspective aims to explore and analyze how these two perspectives shape individual morality and ethics. The research method used is comparative analysis through literature studies covering Islamic religious texts and character education sources from Western traditions. The results of the study show that character education in Islam emphasizes the vertical relationship between individuals and Allah SWT, with an emphasis on the values of honesty, justice, and compassion as the main foundation for character building. In contrast, the Western approach is secular, prioritizing individual autonomy, pluralism, and equality, and is more responsive to social dynamics and the global context. These findings provide deep insights into the philosophical and practical differences in character education, as well as their implications for efforts to build a civilized and harmonious society.